Development of simple sequence repeat markers for Chamerion angustifolium (Onagraceae). (8th May 2019) - Mi, Rui; Wang, Tongcheng; Dunn, Derek W.; Huang, Kang; Li, Baoguo
Abstract : Premise: Rosebay willowherb, or fireweed ( Chamerion angustifolium : Onagraceae), has diploid, tetraploid, and hexaploid cytotypes. There are known physiological and ecological differences among the three cytotypes, but genetic differences remain undetermined. We developed simple sequence repeat (SSR) markers for this species. Methods and Results: Leaf samples were collected from three hexaploid C. angustifolium populations. We successfully amplified 16 SSR loci, which were found to be highly polymorphic. The number of alleles, the observed heterozygosity levels, and the expected heterozygosity levels ranged from four to 13, 0.286–0.899, and 0.372–0.871, respectively. Most primers could also be amplified successfully in C. conspersum and the closely related species Epilobium palustre . Conclusions: The 16 polymorphic SSR markers developed here will be useful for genetic studies in C. angustifolium and related species.